Considerations on the further improvements of regional geoid modeling over the Baltic countries - Ellmann, Artu (Geodesy and Cartography, 2012)
This contribution reviews earlier geoid modeling research in the Baltic countries. The most commonly used modifications of Stokes’s formula are discussed. Similarities and differences between stochastic and deterministic modification methods are outlined. Principles of selecting the geoid modeling methods and parameters are explained and numerically verified. The influences of typical shortages of historic gravimetric datasets to geoid modeling are discussed. Suggestions for further data improvement and enhancements of other geoid modeling aspects are summarized.Baltijos šalių regioninio geoido modeliavimo tobulinimasSantrauka. Straipsnyje peržiūrėta ankstesni Baltijos regiono geoido modeliavimo tyrimai. Aptarta dažniausiai taikomos Stokso formulės modifikacija. Pažymėti panašumai ir skirtumai tarp stochastinio ir deterministinio modifikavimo metodo. Paaiškinti ir skaičiavimais patikrinti geoido modeliavimo metodų ir parametrų parinkimo principai. Aptarti istorinių gravimetrinių duomenų rinkinių tipiniai trūkumai. Apibendrinti pasiūlymai duomenų ir geoido modeliavimo kokybei pagerinti.